Pendampingan Sekolah Sungai Kelurahan Gunung Anyar Tambak Surabaya melalui Program Pojok Literasi - Lintang Laxita Chandra Dewi; Buffon Yoppy Trie Ambodo (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The " Sekolah Sungai " program in Gunung Anyar Tambak, Surabaya, is an initiative by PLN since 2018 to raise literacy and skills among the community of interests around the river. This program includes various activities focused on learning about nature and ways to protect the fence environment. PPK Ormawa HIMANATA, which stimulate the opportunity to supply suffer innovations for learning at the Sekolah Sungai, created introduction in five literacy, fine art, and creative science corners. These include the Calistung Corner, English Corner, Kolase-Diorama Corner, Film Corner, and Art Corner. This study propose to identify the impact of the program on the literacy development of children and the surrounding community, equally substantially as to provide an rating of the strength of each learning corner. This is bear to service as a guideline for the community to prolong the literacy corner program, particularly the foundation within these five literacy corners.